2007
DOI: 10.1016/j.jcrs.2007.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Subconjunctival bevacizumab for vascularized rejected corneal grafts

Abstract: We describe 3 patients who experienced corneal neovascularization following keratoplasty and were treated with a single subconjunctival injection of 2.5 mg bevacizumab. Although there was immediate regression of the corneal vascularization and haze, as well as improvement in the anterior chamber reaction, the effects were short-lived and starting from the second week, the corneal vessels began to progress. All 3 cases ended in permanent graft failure. The series suggests a possible role for bevacizumab in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 9 publications
2
49
0
2
Order By: Relevance
“…A possible role of bevacizumab in the management of graft rejection with vascularization may be discussed, as stated by other authors as well [10].…”
Section: Discussionmentioning
confidence: 78%
“…A possible role of bevacizumab in the management of graft rejection with vascularization may be discussed, as stated by other authors as well [10].…”
Section: Discussionmentioning
confidence: 78%
“…One patient had dry eye and exhibited significantly regression of ve ssels a week after injection, while the other patient had a failed graft and exhibited only minor vessel regression. Awadein (23) descri bed 3 pa tients with corneal neovascularization after keratoplasty who were trea ted with a single subconjunctival injection of 2.5 mg bevacizumab. In all patients, the number and caliber of blood vessels decreased after injection.…”
Section: Discussionmentioning
confidence: 99%
“…Dastjerdi et al 179 noted a decrease in NV area and vessel caliber, but not invasion area, and no effect on VA or central corneal thickness (10 patient series). Awadein 175 noted immediate regression of NV and inflammation, but the effect was transient and short lived, with eventual permanent failure in all 3 patients (rejected PKs). He noted that regression was more marked in patients with smaller and/or fewer blood vessels.…”
Section: Nonsteroidal Anti-inflammatory Agentsmentioning
confidence: 95%
“…None of the studies reported any significant side effects. Clinical reports 146,[175][176][177][178][179][180][181][182][183][184][185][186][187][188][189][190] on anti-VEGF treatment with bevacizumab in CNV have been published. Bevacizumab (Avastin; Genentech, Roche, Switzerland) is a full-length recombinant humanized murine monoclonal antivascular endothelial growth factor antibody (93% human origin and 7% murine origin) that binds to and inhibits biological activity of all human VEGF-A isoforms.…”
Section: Nonsteroidal Anti-inflammatory Agentsmentioning
confidence: 99%
See 1 more Smart Citation